Spiritual Origin of Kazakh Folklore - Әмірқұловa, Ж. А.; Рыскиевa, А. Ә.; Құрaнбек, Ә. А. (Journal of Oriental Studies, 2018)
One of the main sources of research of the Kazakh philosophy and cultural studies is the study of folklore as the basis of folk wisdom and the form of cultural and philosophical knowledge. The Kazakh folklore reflects the life, the meaning of existence, the purposes and nation mindset, the world outlook of the people is revealed. Philosophical problems that contained in folklore, help to know the spiritual content of national culture and are the methodological basis for cultural, philosophical and scientific conclusions. Accordingly, we can affirm the relevance of this article. The worldview of the people is determined by the degree of development of its spirituality. The spiritual heritage of the people includes “folk wisdom”, reflected in folklore. The relevance of the article is to identify the importance of philosophical ideas in folklore and in their theoretical justification. In this regard, in the studies of folklore, taking into account the depth of philosophical thoughts, the most important is the philosophical and ideological analysis of folk art.